Dual-Modality Probes for in Vivo Molecular Imaging - Seulki Lee; Xiaoyuan Chen (Molecular Imaging, 2009)
Various imaging modalities have been exploited and are successfully employed to investigate the anatomic or functional dissemination of tissues in the body. However, no single imaging modality allows overall structural, functional, and molecular information as each imaging modality has its own unique strengths and weaknesses. The combination of two popular imaging modalities that investigates the strengths of different methods might offer the prospect of improved diagnostic and therapeutic monitoring abilities. To date, only a few hybrid systems have become clinically adopted, but there are encouraging signs that the new generation of multimodality systems will be undergoing evaluation in the near future. On the other hand, significant progress has been made toward the creation of dual-modality imaging probes, which can be used as novel tools for future multimodality systems. The interdisciplinary research that couples molecular imaging science to nanotechnology has generated synergistically integrated novel dual-modality imaging probes. These all-in-one probes take full advantage of two different imaging modalities and could provide unique information that impacts preclinical and, eventually, clinical diagnostics. This review discusses the advantages and challenges in developing dual-modality imaging probes and summarizes the current state-of-the-art systems with respect to their unique design strategies and applications.